2020
DOI: 10.1002/acn3.51219
|View full text |Cite
|
Sign up to set email alerts
|

Ring trial of 2nd generation RT‐QuIC diagnostic tests for sporadic CJD

Abstract: Objective: Real-time quaking-induced conversion (RT-QuIC) assays detect prion-seeding activity in a variety of human biospecimens, including cerebrospinal fluid and olfactory mucosa swabs. The assay has shown high diagnostic accuracy in patients with prion disorders. Recently, advances in these tests have led to markedly improved diagnostic sensitivity and reduced assay times. Accordingly, an algorithm has been proposed that entails the use of RT-QuIC analysis of both sample types to diagnose sporadic Creutzfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…The second-generation RT-QuIC, also known as the IQ assay (Improved QuIC), is a version of the assay with increased sensitivity and significantly shorter time of detection [10]. Almost all human studies utilizing second-generation RT-QuIC have used CSF as the analyte [8][9][10][11][15][16][17][18][19][20][21]. In our retrospective study, we evaluated the second-generation RT-QuIC assay for the analysis of archival post-mortem BH and CSF samples within a TSE patient cohort typical of the Czech Republic [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…The second-generation RT-QuIC, also known as the IQ assay (Improved QuIC), is a version of the assay with increased sensitivity and significantly shorter time of detection [10]. Almost all human studies utilizing second-generation RT-QuIC have used CSF as the analyte [8][9][10][11][15][16][17][18][19][20][21]. In our retrospective study, we evaluated the second-generation RT-QuIC assay for the analysis of archival post-mortem BH and CSF samples within a TSE patient cohort typical of the Czech Republic [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence accumulated with prions and more recently with a growing list of other proteins indicate that the misfolded conformers can be amplified with recombinant substrates in a seeded reaction in vitro— a prerequisite step for misfolding propagation in the brain [ 22 , 24 , 29 , 41 , 46 , 63 65 ]. At initial 10 −6 dilution of purified prions, we observed lower ThT fluorescence, and in MM2 prions an extended lag phase after 200ms irradiation ( Fig 3 ).…”
Section: Resultsmentioning
confidence: 99%
“… 113 Overall, these characteristics support the choice by WHO to include the CSF RT-QuIC test in the diagnostic criteria for sCJD. 39 , 99 , 101 As previously mentioned, only few specialized laboratories have adopted the RT-QuIC technology. However, the assay is relatively easy to learn and can be rapidly used by trained personnel, thus consenting its widening in other centers specialized in the diagnosis of neurodegenerative diseases associated with protein misfolding.…”
Section: Discussionmentioning
confidence: 99%
“…55,56,83,92,[95][96][97][98] In 2020, an international trial confirmed the robustness and reliability of the second generation RT-QuIC for the diagnosis of sCJD. 99 Furthermore, a recent article by Fiorini et al 100 demonstrated that through the combined RT-QuIC analysis of the CSF and OM collected from the same sCJD patient it is possible to reach a diagnostic accuracy of 100%. For these reasons, the RT-QuIC has been introduced among the diagnostic criteria of some surveillance centers.…”
Section: Clinical Challengesmentioning
confidence: 99%